Rapid prototyping web applications using Node.js and MongoDB - Krol, Jason; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"Let's rapidly prototype a web application from scratch in as little time as possible! Our prototype will be a fully featured interactive web application that persists data and is written with as few lines of code as possible. In this hands-on webcast you will learn how to leverage Node.js and Express.js to quickly bootstrap a web server, tie in MongoDB to persist data, and display it all using dynamic HTML templates. Finally we'll wrap it with Twitter's Bootstrap framework so it has a nice level of polish!"--Resource description page.
Title from title screen (viewed May 20, 2015).
Date of publication taken from resource description page.
Presenter, Jason Krol.
Keywords: Web applications; Node.js.; MongoDB; Electronic books